STANDAR PROFESI PRAMUSAJI PADA DEPARTEMEN FOOD AND BEVERAGE HOTEL MUTIARA MERDEKA PEKANBARU - Sariyah "; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Standard profession of waiters is an effort in the form of providing services with a special reference that serves as a guide so that all activities run smoothly. In standardizing waiters in the food and beverage department, Mutiara Merdeka Hotel has four main standards, namely appearance standards, attitude and personality standards, competency standards in the field of expertise and waiters' personal equipment standards. This study uses a qualitative method with a descriptive approach. Data collection techniques used in this study were observation, interviews, and documentation. Key informants involved in this research are Mr. Norik Fans as manager of the food and beverage department at Mutiara Merdeka Hotel. Based on the results of the study, Standardization of Waiters at the Food and Beverage Department at Mutiara Merdeka Hotel has gone well in terms of service, appearance, attitude and personality, as well as competence in the field of expertise and personal equipment. Of course there are obstacles in the standardization of the waiters in the form of not using uniforms according to standards, and errors when serving guest orders, but these obstacles can be overcome properly. Keywords: Standardization, waiters, food and beverage department.